As dimensões de apropriação dos bens ambientais sobre a agrobiodiversidade : uma análise à luz da função socioambiental - Miranda, João Paulo Rocha de (2011)
This paper aims to demonstrate that although the legal protection of the environmental good of agrobiodiversity ownership is subject to the principle function of socio-environmental, agricultural biodiversity has been appropriated by transnational biotechnology companies, seed and agricultural inputs. The worst is that this appropriation is legitimized by intellectual property rights, which exploits this process, called the doctrine of a new environmental justice colonization of agrobiodiversity. Thus, this work starts with the evolution of the environmental good of res nullius to res omnium, demonstrating that the current Constitution of the Federative Republic of Brazil adopts a model of ethical anthropocentrism attenuated. Therefore, it is clear that the new constitutional order provides for a new environmental good, not public as prior, but of common use, essential to mankind‘s healthy quality of life and of diffuse nature. It also delimits the bi-dimension of environmental good, as well as regimes of appropriation of agrobiodiversity in the light of social and environmental function. For this purpose, discussions with the legal institutions of property and social and environmental function are made, beginning with the historical aspects of construction and the emergence of this principle to its constitutionalization and internalization in the Brazilian legal system. In this regard aspects of the social function of rural and intellectual properties are evident, particularly the industrial, since it has great importance in the protection of agrobiodiversity. On that matter, it is demonstrated the legitimization that the intellectual property right gives a new form of colonialism which deterritorializes life to privatize it, through the appropriation of agrobiodiversity. Finally, it is demonstrated legal resistance to this colonization process of the agricultural biodiversity.